World History - Wagner,Robin
The book World History has been designed to highlight the course of events in the modern world during nineteenth century. The theme of this book is the relations of the great powers of different countries. The topics like, the First World War, its impacts; the Third French Republic; reasons of Russian Revolution and aftermaths, Washington Conference, position of East Asia, East Europe and West Asia during Second World War have been discussed briefly to ease the students and researchers for their studies.